STRATEGIC EXPLORATION OF POTENTIAL GROWTH FOR THE SELECTION OF NICHES FOR OXALIS SPP. - A. Rashid; T. A. Cheema; A. U. H. Khan; F. Zahid; Z. Bashir; S. A. Mirza; S. Ali (Journal of Animal and Plant Sciences, 2020)
The present study was an endeavor to investigate the growth strategies of Oxalis corniculata L., O. corymbosa DC. and O. pes-caprae L. The distribution and seasonal pattern of growth of Oxalis spp. was followed by regularly harvesting the species and measuring growth parameters on monthly basis at selected sites. It seemed that the growth pattern of the species allows them to select particular niches in the garden. The comparative analysis of life cycle showed that O. corniculata has the longest growing season and reproduce by seeds and vegetative propagules, whereas O. corymbosa and O. pes-caprae have short growing seasons and reproduce by vegetative propagules only. It appeared that O. corniculata is Competitive Ruderal (C-R) garden weed with occurrence on less disturbed areas and its growth strategies allow it to compete with other grasses in the same habitat. Oxalis corymbosa and O. pes-caprae are Stress-Tolerant Ruderals (S-R) as they are found at disturbed sites. Mode of vegetative reproduction of O. corymbosa is more efficient as compared to O. pes-caprae. O. pes-caprae have more specialized niches and spot bound mode of vegetative propagules that make it the most vulnerable in the gardens as compared to the other two species.
Keywords: Oxalis corniculata; Oxalis corymbosa; Oxalis pes-caprae; Growth Strategies; Lahore; Pakistan